Analisis Pengaruh Word Of Mouth Dan Ekuitas Merek Terhadap Keputusan Pembelian Iphone Di Kota Tebing Tinggi - Arifin, Indra Welly; Rajagukguk, Frederick Rudy Sentosa; Harahap, Hastuti Handayani (Management And Business Progress, 2025)
This study aims to determine the effect of word of mouth and brand equity on the decision to purchase an iPhone in Tebing Tinggi City. The research method used is a quantitative method using the help of SPSS version 25.00 which is collected from the results of distributing questionnaires to consumers of the FD Store in Tebing Tinggi City. The analysis method used in this study is to use an instrument test, namely the validity and reliability test. The classical assumption test is the normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, determination coefficient analysis (R2), hypothesis test is the T test and F test. The results of SPSS in this study are word of mouth has an effect on Purchasing Decisions, brand equity does not have an effect on Purchasing Decisions, word of mouth and brand equity have a simultaneous effect on Purchasing Decisions.